Enhanced proportional-resonant current controller for unbalanced stand-alone DFIG-based wind turbines. - Van-Tung Phan (Journal of electrical engineering & technology)
An enhanced control strategy for variable-speed unbalanced stand-alone doubly-fed induction generator-based wind energy conversion systems is proposed in this paper. The control scheme is applied to the rotor-side converter to eliminate stator voltage imbalance. The proposed current controller is developed based on the proportional-rsonant regulator, which is implemented in the stator stationary reference frame. The resonant controller is tuned at the stator synchronous frequency to achieve zero steady-state errors in rotor currents without decomposing the positive and negative sequence components. The computational complexity of the proposed control algorithm is greatly simplified, and control performance is significantly improved. Finally, simulations and experimental results are presented to verify the feasibility and the robustness of the proposed control scheme.